Evidence and Search for Sterile Neutrinos at Accelerators - W. C. Louis (Advances in High Energy Physics)
The LSND short-baseline neutrino experiment has published evidence for antineutrino oscillations at a mass scale of ~1 eV2. The MiniBooNE experiment, designed to test this evidence for oscillations at an order of magnitude higher neutrino energy and distance, observes excesses of events in both neutrino mode and antineutrino mode. While the MiniBooNE neutrino excess has a neutrino energy spectrum that is softer than expected from LSND, the MiniBooNE antineutrino excess is consistent with neutrino oscillations and with the LSND oscillation signal. When combined with oscillation measurements at the solar and atmospheric mass scales, assuming that the LSND and MiniBooNE signals are due to neutrino oscillations, these experiments imply the existence of more than three neutrino mass states and, therefore, one or more sterile neutrinos. Such sterile neutrinos, if proven to exist, would have a big impact on particle physics, nuclear physics, and astrophysics and would contribute to the dark matter of the universe. Future experiments under construction or proposed at Fermilab, ORNL, CERN, and in Japan will provide a definitive test of short-baseline neutrino oscillations and will have the capability of proving the existence of sterile neutrinos.